Hydroxyproline excretion in infantile gastroenteritis. - Begent, R H (1977)
Total hydroxyproline/creatinine ratio (THP:Cr) was measured in random urine specimens from 18 infants with gastroenteritis. THP:Cr was sometimes increased during the acute phase of the illness and the reasons for this are discussed. Seven patients failed to thrive after the acute phase and THP:Cr was low in all of these. The test appears to be a sensitive indicator of the onset of failure to thrive, and it is suggested that it may be of value in the management of these patients.